ANALISA SENSITIVITAS DAN KARAKTERISTIK MASYARAKAT DI KOTA PALEMBANG DALAM MEMILIH MODA TRANSPORTASI DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Dali Kesuma Wicaksana (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2015)
Palembang city as we know it, has been growing rapidly in many aspects, catching up with today's globalized world. Together with this growth, comes a wider variety of public's choice on transportation mode to facilitate their movement from one place to another. Public transports such as angkot, buses, taxis as well as private cars and motorcycles. With Analytical Hierarchy Process (AHP) method, it will be easier to determine the rank of factors that affect the choices of mode as well as to test its sensitivity. Out of 400 responses received, the main factor that affects public's choice on transportation mode is security, which comprises 30% of the total response. 35,5% chooses private cars, making it the main choice. The sensitivity test result has shown that changes in every criteria will change accordingly the graph of other criteria.